2021
DOI: 10.1093/g3journal/jkab363
|View full text |Cite
|
Sign up to set email alerts
|

Genomic studies with preselected markers reveal dominance effects influencing growth traits in Eucalyptus nitens

Abstract: Genomic selection (GS) is being increasingly adopted by the tree breeding community. Most of the GS studies in trees are focused on estimating additive genetic effects. Exploiting the dominance effects offers additional opportunities to improve genetic gain. To detect dominance effects, trait-relevant markers may be important compared to nonselected markers. Here, we used preselected markers to study the dominance effects in a Eucalyptus nitens (E. nitens) breeding population consisting of open-pollinated (OP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Recently, several studies on tree species have reported that selecting markers that have a particular influence over the studied trait could improve the predictive ability (Thumma et al , 2022). Tan and Ingvarsson (2022) (Tan and Ingvarsson, 2022) reported that a careful 1% preselection of markers could improve the estimate of heritability and genomic prediction in a Eucalyptus population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, several studies on tree species have reported that selecting markers that have a particular influence over the studied trait could improve the predictive ability (Thumma et al , 2022). Tan and Ingvarsson (2022) (Tan and Ingvarsson, 2022) reported that a careful 1% preselection of markers could improve the estimate of heritability and genomic prediction in a Eucalyptus population.…”
Section: Discussionmentioning
confidence: 99%
“…latifolia , Cappa et al (2022) reported that selecting informative markers, in particular markers capturing ancestry/population structure, can improve the predictive ability. In Eucalyptus nitens , Thumma et al (2022) developed a marker panel based on selected candidates and genotyped with a “targeted genotyping-by-sequencing (TGD)” method and revealed dominance effects influencing growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies in trees have shown, that GP using a few thousand randomly selected SNPs may capture most of the variation and achieve a similar GP accuracy as using all available markers [ 13 16 ]. It has also been reported that marker preselection could slightly-to-moderately improve GP accuracy in tree species [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%